Designing and evaluating a public engagement activity about sea level rise - N. Vergunst; T. Varol; T. Varol; E. van Sebille (Geoscience Communication)
In this paper, we describe the design process of a public engagement activity about sea level rise aimed at young adults (aged 16 to 25) living in the Netherlands that was intended to reduce participants' psychological distance to sea level rise. We conducted the activity on multiple occasions, including at a science festival and in vocational education classrooms, and performed a statistical analysis of the impact measurement among 117 participants. Based on the analysis and observations, we conclude that the activity resonated well with our target audience, regardless of their level of science capital. We suggest that a design-based research approach is well suited for the development of similar activities and recommend a focus on personal relevance, interactivity, and accessibility in public engagement activities. While the game resonated well with participants, the impact may vary in different educational or cultural contexts, particularly where engagement with sea level rise is low.